Enhancing the luminescence of carbon nanodots in films by tailoring the functional groups through alkylamine-functionalization and reduction. Issue 47 (20th November 2019) - Kim, Minsu; Kang, Phil Woong; Park, Sunjoong; Jeon, Duk Young; Lee, Hyunjoo
Abstract : The luminescence of carbon nanodots in films was enhanced by tailoring functional groups because the energy levels could be significantly simplified. Abstract : Enhancing the luminescence efficiency and stability of solid-state phosphors with facile processability is important for various applications. Carbon-based materials might have proper optical features and durability under ambient conditions. However, carbon-based phosphors usually showed severe quenching of the photoluminescence in the absence of solvent. Alkylamine-functionalization of carbon-based phosphors can alleviate the quenching, but it also resulted in low luminous efficiency. In this study, tailoring the functional groups of carbon nanodots (CNDs) was carefully studied through alkylamine-functionalization and reduction. The reduction with NaBH4 changed the electron-withdrawing functional groups on the alkylamine-functionalized CNDs to electron-donating groups, enhancing the luminescence efficiency. The delicate modulation of alkylamine-functionalization and reduction enabled efficient and robust photoluminescence in the film without any host materials.